Estudo e desenvolvimento de banhos contendo benzotriazol para eletrodeposição de níquel e caracterização química, física e morfologica dos filmes - Moraes, Ana Carolina Mazarin de (2008)
In this work, nickel electrodeposition has been studied in the presence of the additives BTAH and/or EDTA onto platinum substrate from Watts plating bath, at different pH. The deposition and dissolution processes with or without additives were investigated through voltammetric techniques. The deposits obtained from these electrolytic solutions were analyzed by scanning electronic microscopy (SEM), X-ray dispersion (EDX) and X-ray diffraction (DRX). Voltammetric studies showed the presence of additives in the plating bath the deposition current densities decreased. The anodic scan suggested the formation of different nickel crystallographic faces, besides that it also suggested other processes that can occur in parallel with dissolution of deposits. The highest efficiencies of the deposition process were obtained at low jdep for all systems studied. The hydrogen evolution reaction occurs simultaneously to the nickel deposition process since the initial moments. The nickel deposition studies from alkaline solutions that contain high concentration of EDTA showed that the complex NiY2- did not discharge to metallic nickel. The deposits were formed only when EDTA was used in low concentrations (additive proportions). Analysis of the deposits by SEM showed that the best conditions to obtain these deposits were carried out at Ed = -1,0 V or jdep = 2,5 mA cm-2 from nickel solutions at pH 6,0 in the presence of 1,0 x 10-3 mol L-1 BTAH. By EDX analysis we could verify that there was O and Cl incorporation in the deposits. The deposits of nickel morphology depends on the deposition potential and consequently on chemical composition of the deposits.